2017
DOI: 10.1016/j.pec.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of a pre-visit intervention to engage teens in pediatric asthma visits

Abstract: Objective The objectives of this study were to: (a) describe teen feedback on an asthma question prompt list/video intervention designed to motivate teens to be more engaged during visits and (b) examine teen demographics associated with teen acceptance of the intervention. Methods Two hundred and fifty-nine teens ages 11 to 17 with persistent asthma were enrolled into a randomized, controlled trial and assigned to either a standard care or an intervention group where they watched an educational video with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 29 publications
(32 reference statements)
1
25
1
Order By: Relevance
“…The youth then completed a one-page asthma question prompt list, in which they checked off the questions they wanted to ask their provider before their clinic visits. 17 Clinic visits were audiotaped. All youth were interviewed after their medical visits by a research assistant while their caregivers completed a questionnaire.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The youth then completed a one-page asthma question prompt list, in which they checked off the questions they wanted to ask their provider before their clinic visits. 17 Clinic visits were audiotaped. All youth were interviewed after their medical visits by a research assistant while their caregivers completed a questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…To encourage youth to be more actively involved during asthma visits, we created an asthma question prompt list and an educational video intervention. 16 , 17 The intervention seeks to motivate adolescents to ask questions about asthma management to help them understand how to manage their asthma better after leaving the clinic visit. We conducted a randomized, controlled trial of the intervention and found that it significantly improved the youth’s question-asking ability and provider education during asthma visits.…”
Section: Introductionmentioning
confidence: 99%
“…The workshop developed in the current study could be used in continuing education programmes aimed at improving practicing pharmacist confidence and knowledge in communicating with adolescents. Future research should develop further educational material, such as communication checklists and templates to facilitate more effective counselling, and to in turn support pharmacists to empower adolescents to be more involved in discussions with their healthcare providers …”
Section: Discussionmentioning
confidence: 99%
“…Future research should develop further educational material, such as communication checklists and templates to facilitate more effective counselling, and to in turn support pharmacists to empower adolescents to be more involved in discussions with their healthcare providers. [29] Future research should assess workshop applicability in other countries and determine its optimal placement within pharmacy curricula, as well as if the workshop improves objectively measured communication.…”
Section: Discussionmentioning
confidence: 99%
“…The QPL may potentially improve patient participation in decision-making about breast cancer treatment (13). The QPL is user-friendly and requires limited financial and human resources, and can be implemented in a busy care environment (10).…”
Section: Introductionmentioning
confidence: 99%